Wide Margin Excision in Patients with Giant Condyloma Acuminata - Lucky Pratama; Lita Setyowatie; Diah Prabawati Retnani (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
Giant condyloma acuminata (GCA) is one of sexually transmitted infections caused by the Human Papilloma Virus (HPV) infection, specifically HPV types 6 and 11. Giant condyloma acuminata is a rare disease with an incidence of around 0.1%. The age distribution peaked in 25-29 years. The higher prevalence of infection is associated with number of sexual partners, history of chlamydia and gonorrhea infection, smoking and human immunodeficiency virus (HIV) infection. A 24 years old male presented with a cauliflower-like mass on the penis that has been growing slowly for 2 years. Physical examination of the penis revealed a pedunculated reddish verrucous mass, mobile, well-defined, 5x2x1.5 cm in size, and positive acetowhite test. The histopathological picture is in accordance with condyloma acuminata. Surgery with wide margin excision was performed to remove the lump. After 14 days post-surgery, the wound was healed completely without any sign of recurrence.